2020
DOI: 10.3389/fmed.2020.00042
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early vs. Delayed Anakinra Treatment in Patients With Adult Onset Still's Disease and Effect on Clinical and Laboratory Outcomes

Abstract: Background: Aim of this study was to search for any difference in the outcome of patients with adult onset Still's disease (AOSD) treated with anakinra (ANK) in relation with the interval between disease onset and the start of anti-interleukin(IL)-1 treatment and according with the different lines of ANK treatment.Results: No significant differences were identified in the ANK effectiveness and frequency of primary or secondary inefficacy for patients starting ANK within 6 months (p = 0.19, p = 0.14, and p = 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 32 publications
2
23
0
Order By: Relevance
“…To conclude, clinical and therapeutic outcomes are independent of early anakinra treatment initiation. However, faster response to control systemic and articular manifestation may be observed in patients with early intervention after disease onset ( Vitale et al, 2-2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…To conclude, clinical and therapeutic outcomes are independent of early anakinra treatment initiation. However, faster response to control systemic and articular manifestation may be observed in patients with early intervention after disease onset ( Vitale et al, 2-2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the same year, a panel of Italian experts established 11 evidence- and consensus-based statements, including that it is relatively safe and effective to use anti-IL-1 therapies in refractory AOSD patients, especially those with the systemic pattern, and it could be both first and subsequent lines of treatment using biologic agents ( 134 ). An updated study reported that patients could attain better remission in systemic inflammation and joint manifestation if they were treated with IL-1 inhibitors as soon as possible after disease onset ( 135 ).…”
Section: Treatmentmentioning
confidence: 99%
“…However, given the safety of anakinra even at high doses, early and aggressive treatment (i.e. 10 mg/kg/day intravenously) is probably advisable, in line with current management of autoinflammatory diseases and macrophage activation syndrome (Grom et al, 2016;Ravelli et al, 2016;Eloseily et al, 2020;Vitale et al, 2020). Clinical trials of anakinra in COVID-19 are ongoing (i.e.…”
Section: Interleukin Onementioning
confidence: 99%